Anxiety and depression symptoms of medical staff under COVID-19 epidemic in China - Liu, Yuan; Chen, Hongguang; Zhang, Nan; Wang, Xing; Fan, Qinyi; Zhang, Yuling; Huang, Liping; Hu, Bo; Li, Mengqian (Journal of affective disorders, 2021)
•The estimated self-reported rates of anxiety symptoms and depression symptoms among medical staff were 13.3% and 18.4% respectively under COVID-19 epidemic.•Up to 23.9% investigated medical staff reported having anxiety or depression symptoms.•Psychological interventions for medical staff should be integrated into the strategies for fighting COVID-19. It is well known that unexpected pandemic has led to an increase in mental health problems among a variety of populations. In this study, an online non-probability sample survey was used to anonymously investigate the anxiety and depression symptoms among medical staff under the COVID-19 outbreak. The questionnaire included Perceived Stress Scale-10 (PSS-10), Generalized Anxiety Disorder 7-Item Scale (GAD-7) and Patient Health Questionnaire-9 (PHQ-9). Factors associated with anxiety and depression symptoms were estimated by logistic regression analysis. A total of 1090 medical staff were investigated in this study. The estimated self-reported rates of anxiety symptoms, depression symptoms and both of the two were 13.3%, 18.4% and 23.9% respectively. Factors associated with self-reported anxiety symptoms include married status (OR=2.3, 95%CI: 1.2, 4.4), not living alone (OR=0.4, 95%CI: 0.2, 0.7), never confiding their troubles to others (OR=2.2, 95%CI: 1.4, 3.5) and higher stress (OR=14.4, 95%CI: 7.8, 26.4). Factors associated with self-reported depression symptoms include not living alone (OR=0.4, 95%CI: 0.3, 0.7), sometimes/often getting care from neighbours (OR=0.6, 95%CI: 0.4, 0.9), never confiding their troubles to others (OR=2.0, 95%CI: 1.3, 3.0) and higher stress (OR=9.7, 95%CI: 6.2, 15.2). The study was a non-probability sample survey. Besides, scales used in this study can only identify mental health states. Under outbreak of COVID-19, self-reported rates of anxiety symptoms and depression symptoms were high in investigated medical staff. Psychological interventions for those at high risk with common mental problems should be integrated into the work plan to fight against the epidemic.